The 5‐hydroxytryptamine4 receptor enables differentiation of informational content and encoding in the hippocampus. Issue 7 (17th February 2016) - Twarkowski, Hannah; Hagena, Hardy; Manahan‐Vaughan, Denise
ABSTRACT: Long‐term synaptic plasticity, represented by long‐term depression (LTD) and long‐term potentiation (LTP) comprise cellular processes that enable memory. Neuromodulators such as serotonin regulate hippocampal function, and the 5‐HT4 ‐receptor contributes to processes underlying cognition. It was previously shown that in the CA1‐region, 5‐HT4 ‐receptors regulate the frequency‐response relationship of synaptic plasticity: patterned afferent stimulation that has no effect on synaptic strength (i.e., a θm‐frequency), will result in LTP or LTD, when given in the presence of a 5‐HT4 ‐agonist, or antagonist, respectively. Here, we show that in the dentate gyrus (DG) and CA3 regions of freely behaving rats, pharmacological manipulations of 5‐HT4 ‐receptors do not influence responses generated at θm‐frequencies, but activation of 5‐HT4 ‐receptors prevents persistent LTD in mossy fiber (mf)‐CA3, or perforant path‐DG synapses. Furthermore, the regulation by 5‐HT4 ‐receptors of LTP is subfield‐specific: 5‐HT4 ‐receptor‐activation prevents mf‐CA3‐LTP, but does not strongly affect DG‐potentiation. These data suggest that 5‐HT4 ‐receptor activation prioritises information encoding by means of LTP in the DG and CA1 regions, and suppresses persistent information storage in mf‐CA3 synapses. Thus, 5‐HT4 ‐receptors serve to shape information storage across the hippocampal circuitry and specify the nature of experience‐dependent encoding. © 2016 The Authors Hippocampus Published by Wiley Periodicals, Inc.